2015
DOI: 10.1007/s13304-015-0288-1
|View full text |Cite
|
Sign up to set email alerts
|

A new system of microwave ablation at 2450 MHz: preliminary experience

Abstract: The aim of this study was to assess the feasibility of the application of the new system (Emprint Microwave Ablation System, Covidien Boulder, CO, USA) and to identify its advantages. In particular the attention was focused to the spherical ablation zone obtained and its usefulness in terms of effectiveness. The new system is composed of: a 2450 MHz generator that delivers a maximum power of 100 W, a fiberglass antenna and a pump for internally cooled antenna. Ten liver nodules (8 hepatocellular carcinomas and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 18 publications
1
35
1
Order By: Relevance
“…The roundness index transverse was 0.94, meaning that a spherical zone of ablation was consistently achieved. 8 The authors have encountered similar results. ►Fig.…”
Section: Thermosphere Technologysupporting
confidence: 56%
See 1 more Smart Citation
“…The roundness index transverse was 0.94, meaning that a spherical zone of ablation was consistently achieved. 8 The authors have encountered similar results. ►Fig.…”
Section: Thermosphere Technologysupporting
confidence: 56%
“…7 In fact, the most predictable sizes and zones of ablation were achieved at 100 W. Ierardi et al published one of the earliest in vivo series of patients treated with the Emprint Ablation System. 8 These authors demonstrated that the Emprint Ablation System produced technically successful reliable spherical zones of ablation in a short period of time. Ten liver nodules (8 hepatocellular carcinomas and 2 metastases), with a mean diameter of 24.9 mm, were treated percutaneously.…”
Section: Thermosphere Technologymentioning
confidence: 99%
“…Completely cooling the active tip increases antenna reliability and prevents tissue sticking (thermal control). The homogeneous environment around the radiator also prevents the wavelength changes caused by tissue desiccation close to the active tip, thus avoiding comet-shaped ablations (wavelength control) (11,12,17).…”
Section: Discussionmentioning
confidence: 99%
“…The publications currently available concerning the HF system are scarce and consist of an ex vivo temperature monitoring study and one percutaneous and two laparoscopic liver ablation patient series (11,(18)(19)(20). To the best of our knowledge, no reports regarding lung ablations with the new HF system are available.…”
Section: Discussionmentioning
confidence: 99%
“…RFA rapidly became the gold standard in ablation, especially in the treatment of small HCC nodules, at first flanking and eventually replacing percutaneous ethanol injection (PEI) treatments [10] . However, RFA exhibits substantial performance limitations in the treatment of large lesions and/or tumors located near major heat sinks [20,21] : Over the last 5 years, these limitations have been effectively tackled by second and third generation MWA systems, with considerably enhanced characteristics both in terms of treatment controllability and of overall coagulative performance [22][23][24][25] . The purpose of this review is: (1) to provide a brief overview of the key physical and technical aspects of MWA and of the currently available systems; and (2) to gather and discuss the most relevant published data on MWA treatments of HCC nodules in regard to clinical results and to the type and rate of complications, both in absolute terms and in comparison with RFA.…”
Section: Introductionmentioning
confidence: 99%